Heteroleptic copper(I) complexes incorporating sterically demanding diazabutadiene ligands (DABs). Synthesis, spectroscopic characterization and solid state structural analysis. (1st October 2019) - Peppas, Anastasios; Papadaki, Evanthia; Schnakenburg, Gregor; Magrioti, Victoria; Philippopoulos, Athanassios I.
Graphical abstract: The synthesis and characterization of new copper(I) complexes of the general formula [Cu( R DAB dipp )(L COOMe )](PF6 ) is described. These are rare examples of heteroleptic copper(I) complexes comprising the 1, 4-diaza-1, 3-butadiene ligand ( R DAB dipp, R = H, Me; dipp = 2, 6-diisopropylphenyl) and an ancillary α-diimine ligand (L COOMe  = methyl-2-(pyridin-2-yl)-quinoline-4-carboxylate). Abstract: The synthesis, isolation and structural characterization of the novel heteroleptic copper(I) complexes [Cu( R DAB dipp )(L COOMe )](PF6 ) (R = H (3 ), R = Me (4 )) incorporating the sterically demanding 1, 4-diaza-1, 3-butadienes R DAB dipp (R = H, Me; dipp = 2, 6-diisopropylphenyl) is reported.3 and4 were isolated in high yields and spectroscopically characterized. The synthetic strategy includes the in situ reaction of the bis-acetonitrile intermediates [Cu( R DAB dipp )(NCMe)2 ](PF6 ), (R = H (1 ), R = Me (2 )) with the required amounts of the methyl-2-(pyridin-2-yl)-quinoline-4-carboxylate (L COOMe ) that was used as the ancillary ligand.3 and4 are rare examples of heteroleptic copper(I) complexes comprising R DAB dipp and an ancillary α-diimine ligand, while3 is the first crystallographically characterized example of this class of compounds. As a side product during the formation of3 and4, the homoleptic complex [Cu(L COOMe )2 ](PF6 ) (5 ) is detected, that has been independently synthesized, for comparison. All the products were characterized by elemental analysis, FT–IR, UV–Vis and NMR spectroscopy. The molecular structures of2 ·CH2 Cl2, 3 and5 ·CHCl3 were elucidated by single-crystal X-ray diffraction.